Educação ambiental e ensino de matemática: análise de propostas desenvolvidas por docentes dos anos iniciais do ensino fundamental - Daleaste, Rosineide Fátima (2023)
The advancement of environmental problems has an increasingly greater impact on people's lives and there is an urgent need for reflections aimed at recognizing concepts and attitudes to better understand the interrelationships between humans, their cultures and their environment, enabling instruments to implement Environmental Education (EA). Therefore, it is up to the school, which is a privileged space in the construction of cultural and scientific knowledge, to promote the production of values based on the idealization of a sustainable society. From this perspective, we aim to identify the conceptions of early years teachers, from the Municipality of Ramilândia-PR, about EA in order to establish a proposal for continued training that integrates EA and Mathematics Teaching (ME), aiming at the development of contextualized and meaningful teaching practices. To this end, we carried out a bibliographical search, in educational documents and regulations, on the transversal theme EA and how it is articulated with EM aimed at the initial years of Elementary School and, subsequently, we developed a continuing education course that attempted to develop plans classes on the subject. The data collection technique was participatory observation combined with two questionnaires, one that preceded the training course and the other at the end. To read and interpret the data, we used content analysis. The results indicate that teachers have adequate knowledge about EA when compared with the conceptualizations of regulations, in a more simplified way, but when compared with the Teaching of Critical Mathematics, weaknesses were found in their conceptions, ratified by the difficulty of associating EM with EA themes in the preparation of teaching plans, some of which were overcome during the course and in the practice of applying lesson plans in regular classrooms. We concluded that the course emphasized the importance of discussing contextualized mathematical problems with teachers, highlighting the capacity of this curricular component to promote civic and critical education among students. Therefore, this research defends the importance of the teacher as a pedagogical mediator, contributing to students' knowledge and learning through the theme of Environmental Education in the Mathematics discipline.